Wind energy : renewable energy and the environment - Nelson, Vaughn. (Energy and the environment (Boca Raton, Fla.)., 2014)
"This new edition adds a chapter on distributed wind power generation, and the rest of the material will be updated throughout. Also, it adds practical uses for wind power, such as municipal street lighting, industrial refrigeration, telecommunications, etc. It will also examine the history of wind energy, and provide ample reasons to shift from fossil fuels to renewable energy. It will cover the characteristics of wind, such as shear, power potential, and turbulence, and discuss the measurement and siting of individual wind turbines and wind farms. The text will present the design, aerodynamics, operation, control, applications, and different types of wind turbines. It will also explore the wind industry from its inception in the 1970s to today as well as the political and economic factors regarding the adoption of wind as an energy source. "--